The stress and mathematics (Revista Electrónica REDINE, 2018)
This article refers to as stress interferes with learning of mathematics. Stressful situations are part of the daily routine of a person's life , the stress level can vary depending on situations or family problems, working , among others, when this level is high you may feel anxiety, this can be caused both internal external or situational stimuli. Stress comes in different people and even in children (as), Trianes (1999) points out the areas in which children can experience stress, they are: the family, the school and the surrounding environment. It is very normal to experience stress when the time to spend time learning math, which is why teachers have a reason to learn the math , taking into consideration the feelings and emotions to facilitate students in learning that subject without sounding cause stress in the acquisition of   knowledge.
Keywords: stress; mathematics; learning; process